Exploration of the binding between ellagic acid, a potentially risky food additive, and bovine serum albumin. (December 2019) - Liu, Fengru; Zhang, Yiyin; Yu, Qiuyang; Shen, Yizhong; Zheng, Zhi; Cheng, Jieshun; Zhang, Wencheng; Ye, Yingwang
Abstract: Ellagic acid (EA), a natural plant polyphenol, is usually used as a functional additive in variety of health foods. However, the potential toxicity of EA to human health should be paid enough attention. To clarify its biological toxicity in vivo, this study explored the binding mechanism of EA with bovine serum albumin (BSA) by means of spectroscopic approaches and molecular docking insimulative physiological conditions. The results showed that the mixture of BSA with EA could spontaneously cause the formation of BSA-EA complex through electrostatic interaction under simulative physiological conditions (0.01 mol·L −1 Tris-HCl, 0.015 mol L −1 NaCl, pH = 7.4). Molecular docking experiments revealed that EA was primarily bound to the hydrophobic pocket of the site I (subdomain IIA) of BSA. It has been reported that the binding of small functional molecules to serum albumins remarkably impacts their absorption, distribution, metabolism, and excretion features. Therefore, this study might be helpful for human to have an in-depth understanding of the biological effect of EA in vivo and guide human to take it safely and reasonably. Highlights: Exploring the interactionmechanismof EA to BSA by spectroscopic approaches. Revealing EA primarily binds to the site I (subdomain IIA) of BSA. Helping us apprehend the transportation mechanism and toxicity of EA in vivo.